2016
DOI: 10.1177/0305735616659553
|View full text |Cite
|
Sign up to set email alerts
|

‘It gives them a place to be proud’ – Music and social inclusion. Two diverse cases of young First Nations people diagnosed with autism in British Columbia, Canada

Abstract: PostprintThis is the accepted version of a paper published in Psychology of Music. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination. Educational Studies, Karlstad University, Sweden. School of Educational Sciences and Psychology, University of Eastern Finland, Joensuu, Finland. 1"It gives them a place to be proud" -Music and social inclusion. Two diverse cases of young First Nations people diagnosed with autism in British Columbia, Canada. Abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 29 publications
0
30
0
2
Order By: Relevance
“…Small sample size. Lindblom, 2017 (Canada) [ 67 ] C Article: ‘It gives them a place to be proud’- Music and social inclusion. Two diverse cases of young First Nations people diagnosed with autism in British Columbia, Canada.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small sample size. Lindblom, 2017 (Canada) [ 67 ] C Article: ‘It gives them a place to be proud’- Music and social inclusion. Two diverse cases of young First Nations people diagnosed with autism in British Columbia, Canada.…”
Section: Resultsmentioning
confidence: 99%
“…The studies described in six of the articles showed positive outcomes associated with the implementation and evaluation of programs designed specifically for Indigenous people with ASD, including improvements in personal (e.g., mood, self-esteem, relaxation, self-regulation, executive functioning; see Table 1 Bettag (Article A) [65] described a program that aimed to improve the developmental (cognitive and communication) outcomes of young children with developmental delay by strengthening parent/caregiver-child relationships and enhancing parenting and teaching skills, and used validated self-report scales and semi-structured observational assessments to measure outcomes. Other articles, Keightley et al (Article B) [66] and Lindblom (Articles C & D) [67,68] used theatre-based activities or traditional and non-traditional music in programs with Indigenous children with developmental impairment or ASD. According to observational reports from researchers, and anecdotal evidence gathered from interviews with participants and caregivers, the programs achieved increased inclusion, improved mood, and increased relaxation in participants.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Through key people in Indigenous education and tribal contexts, research partners were found. This access was made possible through my family connections with the Lake Babine Nation in BC, Canada (see Lindblom, 2016, 2017a, 2017b).…”
Section: Methodsmentioning
confidence: 99%
“… 1. The cases can also be found in Lindblom (2016, 2017a, 2017b) and Dindar, Lindblom, and Kärnä (2017). …”
mentioning
confidence: 89%
“…Twenty-four articles were included. Seven articles explore identity and experiences of autistic Indigenous Peoples (Bailey & Arciuli, 2020;Kapp, 2011;Lindblom, 2014Lindblom, , 2017aLindblom, , 2017bSullivan, 2013;Travers et al, 2013). Ten articles explore autistic identity (Cooper et al, 2017;Cridland et al, 2014;DeNigris et al, 2018;Hughes, 2012;Kapp et al, 2013;MacLeod et al, 2013;Mogensen & Mason, 2015;Tan, 2018;Violeta & Langer, 2017;Winstone et al, 2014), five articles, Indigenous identity (Kahn et al, 2016;Kelley & Lowe, 2018;Kickett-Tucker et al, 2015;Tracey, 2012;Victor et al, 2016), and two articles, the inclusion and treatment of Indigenous students with a variety of disabilities (Bevan-Brown, 2013;Graham, 2012).…”
Section: Literature Searchmentioning
confidence: 99%